Industrial training report: Bahagian Hal Ehwal Akademik (HEA) Universiti Teknologi MARA (Kelantan) / Wan Muhammad Safuan Alauddin Wan Suhaimi - Wan Suhaimi, Wan Muhammad Safuan Alauddin (Perpustakaan Tengku Anis, 2017)
In this report, its provide a comprehensive description about the practical training which is are being carried out at Bahagian Hal Ehwal Akademik (HEA), UiTM Machang Kelantan for 5 month period. There are 4 chapter's content which include introduction to an organization which are UiTM Machang and Bahagian Hal Ehwal Akademik (HEA). Various department which carry a different role and different job scopes, than the activities that are carried out during the practical training and lastly the lesson gained during the time period of training.